Comparative Study of Flipped Classroom in IPAS-Based Thematic Learning for Elementary School Teacher Candidates Using The Scriven Model - Ida Ermiana; Asri Fauzi; Aisa Nikmah Rahmatih; I Gede Ratnaya (BIOCHEPHY: Journal of Science Education, 2026)
The Scriven evaluation model consists of formative and summative evaluations. In this study, the Scriven model was employed to examine differences in the implementation of the learning process in the IPAS-based Thematic Learning course that applied the flipped classroom model and those that did not, as well as to describe the comparative results of formative and summative evaluations in the course. This research adopted a comparative case study approach involving 75 students from the Elementary School Teacher Education Program at the University of Mataram. The formative evaluation results in the class implementing the flipped classroom within IPAS-based thematic learning demonstrated relatively stable average scores and mastery percentages, with only a 1% difference in mastery at the fourth formative assessment, while the first through third formative assessments showed the same average mastery rate of 20%, indicating that the application of the flipped classroom was able to maintain consistency in learning outcomes and ensure continuous mastery of IPAS content. In contrast, the IPAS-based thematic learning class that did not implement the flipped classroom exhibited considerable fluctuations in formative evaluation results, with average scores and mastery levels of 80.5 and 21% in the first formative assessment, 88.8 and 23% in the second, 78 and 20% in the third, and the lowest average score of 64.76 with a mastery level of 16% in the fourth formative assessment. These disparities in formative outcomes subsequently affected the summative evaluation results, in which the average summative score of the class implementing the flipped classroom in IPAS-based thematic learning was higher than that of the class without the flipped classroom, at 82.243 compared to 78.594, with a difference of 3.649. These findings indicate that the implementation of the flipped classroom contributes positively to the stability of the learning process and to the learning outcomes of prospective elementary school teachers.